Preparation and evaluation of an innovative antibacterial bi-layered composite dressing for skin wound healing. Issue 3 (August 2021) - Sun, Leilei; Li, Mingbo; Gong, Tengfei; Feng, Jianling
Abstract: Aim of the study: The aim of the current study was to develop collagen-based bi-layered composite dressings with antibacterial property and evaluate the efficiency for wound healing. Materials and methods: A bi-layered composite wound dressing was fabricated using two marine biomacromolecules (collagen and chitosan or carboxymethyl chitosan). Non-crosslinked and N-Ethyl-N'-(3-dimethylaminopropyl) carbodiimide/N-Hydroxy succinimide (EDC/NHS) cross-linked collagen sponges fabricated by vacuum freeze-drying technology was used as the inner layer. The medical spun-laced nonwoven coated with chitosan and carboxymethyl chitosan was used as the outer layer. The antibacterial activities against E. coli and S. aureus were evaluated by the inhibition zone assay. Deep second-degree scald model was performed to evaluate the efficiency of bi-layered composite dressings for wound healing. Results: In view of comprehensive evaluation of appearance and in vitro antibacterial activity, medical spun-laced nonwoven coated with 3% of chitosan solution was chosen to be used as the optimized preparation conditions to produce the outer layer of composite dressing, which acted as a barrier against microorganisms and provided mechanical support. Furthermore, the results of wound closure and histopathological analysis indicated that EDC/NHS cross-linked collagen-based bi-layered composite dressing was superior to non-crosslinked and commercial products, which stimulated the wound healing process and accomplished deep second-degree scalded skin healing within a time span of 28 days. Conclusion: The EDC/NHS cross-linked collagen-based bi-layered composite dressing had immense potential to be applied for an ideal wound dressing for more efficient and faster wound healing. Therefore, the findings provided the essential theoretical basis for great potential of collagen-based composite dressing used in wound healing applications. Highlights: Collagen-based bi-layered composite dressings accelerated skin wound healing. Collagen and chitosan could be applied for an ideal antibacterial wound dressing. EDC/NHS cross-linked collagen-based dressing was superior to non-crosslinked. EDC/NHS cross-linked collagen-based dressing was superior to commercial product.